Immediate effect of selective neuromuscular electrical stimulation on the electromyographic activity of the vastus medialis oblique muscle - Jamilson Simões Brasileiro; João Felipe de Souza Nogueira; Denise Dal'Ava Augusto (Universidade Federal de Santa Catarina, 2008)
The Patellofemoral pain syndrome (PFPS) is described as an anterior or retropatellar knee pain in the absence of other associated diseases, and has often been associated with dysfunction of the vastus medialis oblique muscle (VMO). However, several studies have demonstrated the impossibility of selectively activating this muscle with exercises. The aim of the present study was to analyze the immediate effect of neuromuscular electrical stimulation of VMO muscle by means of monitoring the electromyographic activity of the vastus medialis oblique (VMO) and vastus lateralis (VL) muscles. Eighteen healthy women with a mean age of 23.2 years and mean BMI of 20 Kg/m2 were evaluated. The study protocol included electromyographic analysis of VMO and VL muscles, before and immediately after neuromuscular electrical stimulation of the VMO muscle. During the electromyographic analysis, the volunteers performed maximal voluntary isometric contraction in a 60° knee extension on an isokinetic dynamometer. "Russian current" apparatus was used for electrical stimulation. Results: The data analysis demonstrated a signifi cant increase in VMO activation intensity immediately after it had been electrically stimulated (p=0.0125), whereas VL activation intensity exhibited no signifi cant increase (p=0.924). Moreover, a significant increase in the VMO/VL ratio was also detected (p=0.048). In this study it was observed that electrical stimulation modifiedthe VMO/VL ratio, which suggests electrical stimulation has a benefi cial effect on VMO muscle strength. Resumo A Síndrome da dor patelofemoral (SDPF) é descrita como dor anterior ou retro-patelar do joelho na ausência de outras patologias associadas, sendo freqüentemente associada à disfunção do Vasto Medial Oblíquo (VMO). Entretanto, diversos estudos têm demonstrado a impossibilidade de ativar seletivamente este músculo através de exercícios. O objetivo do presente estudo foi analisar o efeito imediato da estimulação elétrica neuromuscular (EENM) seletiva no músculo VMO por meio do comportamento eletromiográfico dos músculos VMO e vasto lateral (VL). Foram avaliadas 18 mulheres saudáveis, com idade média de 23,2 anos e IMC médio de 20 Kg/m2. Os procedimentos do estudo incluíram uma análise eletromiográfica dos músculos VMO e VL, antes e imediatamente após a EENM do músculo VMO. Durante a análise eletromiográfica, as voluntárias realizaram uma contração isométrica voluntária máxima durante a extensão do joelho a 60° em um dinamômetro isocinético. A estimulação elétrica foi realizada através da corrente Russa. A análise dos dados mostrou um aumento significativo na intensidade de ativação do músculo VMO imediatamente após a estimulação do mesmo (p=0,0125), enquanto que a intensidade de ativação do músculo VL, não mostrou aumento significativo (p=0,924). Além disso, verificou-se também um aumento significativo na relação VMO/VL (p=0,048). No presente estudo, observou-se uma modificação na relação VMO/VL após a EENM, sugerindo que a mesma tem um efeito favorável no fortalecimento seletivo do VMO.